Analysis of Language Politeness of Social Media Users on Instagram Anies Rasyid Baswedan - Muhamad Farik Soumena; Suhardi (Britain International for Academic Research (BIAR) Publisher, 2023)
Language is a communication tool owned by humans to interact or collect. From a language humans can exchange information orally and in writing. The development of technology is growing in various countries, including Indonesia, resulting in the process of communication and exchanging information between people from various regions and parts of the world. A speaker must use courteous or good language when communicating through mass media for speech partners who are intended recipients of the message to be able to interpret and comprehend the message. This study aims to describe the utterances of social media users in the Anies Rasyid Baswedan Instagram comment column, which allegedly contain the principle of language politeness. This is a type of qualitative descriptive research. The method used in this study is data analysis, according to Miles and Huberman, namely, data reduction, data presentation, and drawing or verifying conclusions. The results of this study found that there were 16 maxims of wisdom, 20 maxims of generosity, 13 maxims of appreciation, 10 maxims of moderation, 18 maxims of consensus, and ten maxims of sympathy.